Penerapan Sistem Lampu Jalan Automatis Berbasis Sensor Cahaya Dengan Integrasi IoT - Mhd Rizki Syahputra; Andri Syahputra; Mangiring Hokkop Kristofer Sitinjak; Fitri Febriadi Turnip; Muhammad Habib (Management of Information System Journal, 2026)
The development of Internet of Things (IoT) technology provides significant opportunities in automation systems, including public street lighting systems. Manual operation of street lights often causes energy waste because the lights remain active when unnecessary. This research aims to design and implement an automatic street lighting system based on light sensors integrated with IoT using NodeMCU ESP8266 and Light Dependent Resistor (LDR) sensors. The system is designed to automatically control the lights based on environmental light intensity and provide real-time monitoring through the Blynk application. The research method used is an experimental method involving hardware design, programming, implementation, and testing stages. The results show that the system can accurately detect changes in light intensity and automatically control the street lights according to environmental conditions. In addition, monitoring data can be displayed in real-time through the Blynk application via internet connectivity. The system also improves energy efficiency because the lights only operate when needed. Based on testing results, the system works properly, stably, and has potential applications in smart lighting and smart city infrastructure.